2020
DOI: 10.5194/acp-20-11869-2020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term time series of Arctic tropospheric BrO derived from UV–VIS satellite remote sensing and its relation to first-year sea ice

Abstract: Abstract. Every polar spring, phenomena called bromine explosions occur over sea ice. These bromine explosions comprise photochemical heterogeneous chain reactions that release bromine molecules, Br2, to the troposphere and lead to tropospheric plumes of bromine monoxide, BrO. This autocatalytic mechanism depletes ozone, O3, in the boundary layer and troposphere and thereby changes the oxidizing capacity of the atmosphere. The phenomenon also leads to accelerated deposition of metals (e.g., Hg). In this study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 87 publications
3
25
0
Order By: Relevance
“…Similarly, Koo et al (2012) studied advection of the O 3 -depleted air masses and found that these events were driven by local or short-range (1 d) transport from the nearby region. A recent study of Bougoudis et al (2020) explored connection between firstyear sea ice and bromine explosion events. In spring (March, April, May) 2017, Arctic mean tropospheric BrO VCDs over sea ice were on the order of 4 × 10 13 molec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Koo et al (2012) studied advection of the O 3 -depleted air masses and found that these events were driven by local or short-range (1 d) transport from the nearby region. A recent study of Bougoudis et al (2020) explored connection between firstyear sea ice and bromine explosion events. In spring (March, April, May) 2017, Arctic mean tropospheric BrO VCDs over sea ice were on the order of 4 × 10 13 molec.…”
Section: Discussionmentioning
confidence: 99%
“…In spring (March, April, May) 2017, Arctic mean tropospheric BrO VCDs over sea ice were on the order of 4 × 10 13 molec. cm −2 , and significant anomalies of tropospheric BrO VCDs were observed over the sea ice north of Svalbard at approximately 85 • N. In addition to the sea-ice conditions, the tropospheric BrO plume formation depends on various meteorological factors and the amount of blowing snow (Bougoudis et al, 2020). To investigate these processes, the weather regime approach presented in the current study may be applied together with the long-term BrO remote-sensing data and in situ measurements from the Arctic stations in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the type of surface covered by snow may be an important factor. Snow covering first-year (FY) ice, ice freshly formed in the previous winter, was found to correlate with bromine producing sites (Simpson et al, 2007;Abbatt et al, 2012;Bougoudis et al, 2020) in contrast to multi-year (MY) ice. Despite that, bromine activation over MY ice was observed as well (Peterson et al, 2019).…”
Section: (R15)mentioning
confidence: 99%
“…Ozone depletion events (ODEs) commonly occur in the Arctic boundary layer during spring. The ozone mixing ratio is reduced from its background level of approximately 30-60 nmol mol −1 to possibly zero levels coinciding with an increase in the bromine concentrations (Oltmans, 1981;Bottenheim et al, 1986;Barrie et al, 1988;Hausmann and Platt, 1994;Wagner and Platt, 1998;Richter et al, 1998;Wagner et al, 2001;Frieß et al, 2004;Wagner et al, 2007;Helmig et al, 2012;Halfacre et al, 2014;Zhao et al, 2016;Blechschmidt et al, 2016;Seo et al, 2019Seo et al, , 2020Bougoudis et al, 2020). The ozone depletion is of special interest since ozone is a very important trace gas due to its role in air pollution and its high oxidation potential.…”
Section: Introductionmentioning
confidence: 99%
“…( 2013 ) reported the photo‐chemical production of molecular bromine from surface snow using chemical ionization mass spectroscopy (CIMS) based on Arctic snow chamber experiments. It has also been shown that bromine activation correlates with the occurrence of first‐year sea ice (Bougoudis et al., 2020 ; Simpson, Carlson, et al., 2007 ), and that it can also occur over snow found on multi‐year sea ice (Peterson et al., 2019 ). These surfaces are similar in that both first year and multi year ice are usually snow covered.…”
Section: Introductionmentioning
confidence: 99%